Targeting the phosphorylation site of myristoylated alanine‐rich C kinase substrate alleviates symptoms in a murine model of steroid‐resistant asthma - Wang, Chien‐Neng (Br J Pharmacol, 2019)
BACKGROUND AND PURPOSE: Myristoylated alanine‐rich C kinase substrate (MARCKS), a PKC substrate, facilitates mucus production and neutrophil migration. However, the effects of therapeutic procedures targeting the phosphorylation site of MARCKS on steroid‐resistant asthma and the mechanisms underlying such effects have not yet been investigated. We designed a peptide that targets the MARCKS phosphorylation site (MPS peptide) and assessed its therapeutic potential against steroid‐resistant asthma. EXPERIMENTAL APPROACH: Mice were sensitized with ovalbumin (OVA), alum, and challenged with aerosolized OVA five times a week for 1 month. The mice were intratracheally administered MPS peptides three times a week, 1 hr before OVA challenge. Asthma symptoms and cell profiles in the bronchoalveolar lavage were assessed, and key proteins were analysed using Western blotting. KEY RESULTS: Phosphorylated (p)‐MARCKS was highly expressed in inflammatory and bronchial epithelial cells in OVA‐immunized mice. MPS peptide reduced eosinophils, neutrophils, mucus production, collagen deposition, and airway hyper‐responsiveness. Dexamethasone (Dexa) did not alleviate steroid‐resistant asthma symptoms. MPS peptide caused a decrease in p‐MARCKS, nitrotyrosine and the expression of oxidative stress enzymes, NADPH oxidase dual oxidase 1 and inducible NOS, in lung tissues. Compared to Dexa, MPS peptides inhibited C5a production and attenuated IL‐17A and KC production in the airway more effectively, thus suppressing asthma symptoms. CONCLUSIONS AND IMPLICATIONS: Our findings indicate that targeting MARCKS phosphorylation through MPS treatment may inhibit neutrophilic inflammation and relieve asthma symptoms, thereby highlighting its potential as a therapeutic agent for steroid‐resistant asthma.